How long till September? - Simon, Tanya Sevilla; Posadas, Jill Arwen (Quezon City Adarna House, Inc., 2010)
"A girl enjoys the different activities each month brings, but deep in her heart she wonders about one thing: how long till September?"
"A book in 2 languages." -- Cover.
This book is recommended for children ages 8 and above.
Text in English and Filipino.
Keywords: Children's stories, Philippine (English); Children's stories, Filipino